1982
DOI: 10.1136/bmj.285.6339.419
|View full text |Cite
|
Sign up to set email alerts
|

Pads and pants for urinary incontinence.

Abstract: Fifty-one female patients, incontinent of urine, were asked to compare two different combinations of pants and pads used in the ambulatory management of their incontinence. They were offered the Kanga pant with a Kanga pad and the Sandra pant with a Bambi pad. Each patient tried both pants and pads and thus comparisons could be made on a within-patient basis. Both systems kept a similar proportion of patients dry during the day and night. In terms of comfort, however, the Kanga pant was quite clearly preferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Some studies considered the effectiveness or acceptability of the special stretch mesh or pouched pants that hold some pads in position, but results were inconclusive. 38,39,49,[55][56][57]59,[67][68][69][70] The consensus is that assessment of individual consumer requirements is the key to appropriate product selection. Indeed, many research articles have emphasized that the particular needs and contexts of individual consumers should guide selection of an appropriate bodyworn pad.…”
Section: Type Of Study Outcomementioning
confidence: 99%
“…Some studies considered the effectiveness or acceptability of the special stretch mesh or pouched pants that hold some pads in position, but results were inconclusive. 38,39,49,[55][56][57]59,[67][68][69][70] The consensus is that assessment of individual consumer requirements is the key to appropriate product selection. Indeed, many research articles have emphasized that the particular needs and contexts of individual consumers should guide selection of an appropriate bodyworn pad.…”
Section: Type Of Study Outcomementioning
confidence: 99%
“…Eleven studies of pant/pad systems were found from 1972 to 1987, with ten reported from Great Britain 6,17–26 . Two specific systems were the focus of study in all the trials, sometimes comparatively, other times in contrast to non‐pant/pad systems.…”
Section: Pant/pad Systemmentioning
confidence: 99%
“…The performance and convenience of such materials are improving, but no comparative trials have been performed on which products are the best 12,13 …”
mentioning
confidence: 99%